Turkey's Future Transitions : Republic of Turkey Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
Turkey made significant progress in poverty reduction and shared prosperity in the 2000s, but poverty is still an important challenge, particularly in some regions. Poverty and extreme poverty has decreased significantly in the past few years. This decrease in poverty was shared across both urban and rural areas. For the next ten years, the Bank will focus on several things. These include who will likely be the poor and the bottom 40, what will be the engine of growth and how growth can be sustainable.